Chemoradiotherapy in geriatric patients with squamous cell carcinoma of the esophagus: Multi-center analysis on the value of standard treatment in the elderly - Bostel, Tilman; Akbaba, Sati; Wollschläger, Daniel; Mayer, Arnulf; Nikolaidou, Eirini; Murnik, Markus; Kirste, Simon; Rühle, Alexander; Grosu, Anca-Ligia; Debus, Jürgen; Fottner, Christian; Moehler, Markus; et al. (Frontiers in Oncology, 2023)
Background and purpose To evaluate the tolerability and outcomes of chemoradiation in elderly patients with locally advanced esophageal squamous cell carcinoma (ESCC). Materials and methods This multi-center retrospective analysis included 161 patients with SCC of the esophagus with a median age of 73 years (range 65-89 years) treated with definitive or neoadjuvant (chemo)radiotherapy between 2010 and 2019 at 3 large comprehensive cancer centers in Germany. Locoregional control (LRC), progression-free survival (PFS), distant metastasis-free survival (DMFS), overall survival (OS), and treatment-associated toxicities were analyzed, and parameters determining patient outcomes and treatment tolerance were assessed. Results The delivery of radiotherapy without dose reduction was possible in 149 patients (93 %). In 134 patients (83%), concomitant chemotherapy was initially prescribed; however, during the course of therapy, 41 % of these patients (n = 55) required chemotherapy de-escalation due to treatment-related toxicities. Fifty-two patients (32%) experienced higher-grade acute toxicities, and 22 patients (14%) higher-grade late toxicities. The 2-year LRC, DMFS, PFS, and OS rates amounted to 67.5%, 33.8%, 31.4%, and 40.4%, respectively. Upon multivariate analysis, full-dose concomitant chemotherapy (vs. no or modified chemotherapy) was associated with significantly better DMFS (p=0.005), PFS (p=0.005) and OS (p=0.001). Furthermore, neoadjuvant chemoradiotherapy followed by tumor resection (vs. definitive chemoradiotherapy or definitive radiotherapy alone) significantly improved PFS (p=0.043) and OS (p=0.049). We could not identify any clinico-pathological factor that was significantly associated with LRC. Furthermore, definitive (chemo)radiotherapy, brachytherapy boost and stent implantation were significantly associated with higher-grade acute toxicities (p<0.001, p=0.002 and p=0.04, respectively). The incidence of higher-grade late toxicities was also significantly associated with the choice of therapy, with a higher risk for late toxicities when treatment was switched from neoadjuvant to definitive (chemo)radiotherapy compared to primary definitive (chemo)radiotherapy (p<0.001). Conclusions Chemoradiation with full-dose and unmodified concurrent chemotherapy has a favorable prognostic impact in elderly ESCC patients; however, about half of the analyzed patients required omission or adjustment of chemotherapy due to comorbidities or toxicities. Therefore, the identification of potential predictive factors for safe administration of concurrent chemotherapy in elderly ESCC patients requires further exploration to optimize treatment in this vulnerable patient cohort.